Reset in Stone : Memory and Reuse in Ancient Athens - Rous, Sarah A. (Book collections on Project MUSE., 2019)
This book examines the various ways ancient Athenians purposefully reused stone artifacts, objects, and buildings in order to shape their own and their descendants' collective ideas about their community's past and its bearing on the present and future. The book introduces the concept of "upcycling" to refer to this intentionally meaningful reuse, where evidence is preserved of an intentionality behind the decision to re-employ a particular object in a particular new context, often with implications for the shared memory of a group. Utilizing archaeological, literary, and epigraphic evidence, this investigation connects seemingly disparate cases of upcycling over eight centuries of Athenian history, treating the city as a continuously evolving cultural community. In establishin g upcycling as a distinct phenomenon of intentionally meaningful reuse, this study offers a process- and agency-focused alternative to the traditional discourses on spolia and reuse, while also making a substantial contribution to the growing field of memory studies by identifying a crucial component within the overall "work of memory" within a community. Through an original interdisciplinary approach, the book illuminates a vital practice through which Athenians shaped social memory in the physical realm, literally building their history into their city